2006
DOI: 10.1007/s00134-006-0492-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of melatonin on endotoxemia-induced intestinal apoptosis and oxidative stress in infant rats

Abstract: Melatonin diminished the intestinal oxidative stress and apoptotic damage induced by endotoxemia in infant rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 39 publications
2
24
0
1
Order By: Relevance
“…Coopersmith et al (2002a, b) found that decreasing intestinal apoptosis improved survival in septic mice subjected to cecal ligation and puncture. In the present study, we also found that administration of LPS into infant rats induced a significant apoptosis in both intestinal epithelium and lamina propria, which is consistent with previous studies (Cinel et al 2002;Ozdemir et al 2007).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Coopersmith et al (2002a, b) found that decreasing intestinal apoptosis improved survival in septic mice subjected to cecal ligation and puncture. In the present study, we also found that administration of LPS into infant rats induced a significant apoptosis in both intestinal epithelium and lamina propria, which is consistent with previous studies (Cinel et al 2002;Ozdemir et al 2007).…”
Section: Discussionsupporting
confidence: 94%
“…This condition results in the mitochondrial damage, which leads to release of cytochrome C, caspase activation, and then apoptotic cell death (Leon et al 2004(Leon et al , 2005. We have previously demonstrated that endotoxemia induced lipid peroxidation in intestinal tissues and therapy strategies that protect oxidative stress attenuated intestinal apoptotic damage in infant rats (Ozdemir et al 2007). As mentioned above, Rho kinase demonstrated to play a regulatory role for apoptosis of various cell types (Shi and Wei 2007).…”
Section: Discussionmentioning
confidence: 96%
“…injections of melatonin and the other received vehicle. Melatonin (20 mg/kg) was dissolved in 5% ethanol in saline (Ozdemir et al, 2007, Olivier et al, 2009) and administered 5 minutes after LPS injection. A total of 72 rats from six litters were used in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Higher superoxide and lipid peroxide production including malondialdehyde (MDA), 4‐hydroxylalkenal and thiobarbituric acid reactive substances are a common result of LPS toxicity. These perturbations appear concomitantly with lower total antioxidant capacity levels including reduced activity of SOD and glutathione peroxidase (GPx) (Crespo et al , ; Paskaloglu et al , ; Wang et al , ; Yerer et al , ; Carrillo‐Vico et al , ; Sener et al , ; Escames et al , ; Ozdemir et al , ; Shang et al , ; Erbas et al , ). LPS‐induced oxidative damage is further confirmed by histological examination of the related tissues (Sener et al , ).…”
Section: Protective Mechanisms Of Melatonin Against Sepsismentioning
confidence: 99%